1968
DOI: 10.1136/bmj.3.5611.146
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Residues in Human Fat in Great Britain

Abstract: Acute Myocardial Infarction-Norris et al. MEDICA JOURNAL dying, heart failure on admission, as determined clinically and radiologically, being nearly as likely to result in death from arrhythmia as in death from failure. Patients suffering late arrhythmic death were, however, much more ill than the survivors, having a greatly increased incidence of shock and heart failure, and a greater incidence of transmural infarction, particularly involving the anterior part of the heart. A detailed analysis of our 70 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

1970
1970
1999
1999

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
1
7
1
1
Order By: Relevance
“…For the BHC isomers and dieldrin the mean amounts found in female subjects of 60 years old and under were significantly less than those for females over 60 years old and for all male subjects. Similar sex differentiation was noted in the previous study (Abbott et al, 1968).…”
Section: -2supporting
confidence: 77%
See 3 more Smart Citations
“…For the BHC isomers and dieldrin the mean amounts found in female subjects of 60 years old and under were significantly less than those for females over 60 years old and for all male subjects. Similar sex differentiation was noted in the previous study (Abbott et al, 1968).…”
Section: -2supporting
confidence: 77%
“…sss Conclusions It is again gratifying to record that the mean concentrations of the residues of the three main organochlorine pesticides found in human fat-namely, BHC, dieldrin, and DDT-have continued to decrease over recent years. It is worth repeating that a similar decline has been concurrently seen in the amounts of these compounds occurring in some fatty foodstuffs consumed in the United Kingdom, thus supporting the previously expressed belief that dietary sources are the main factor in determining the residue levels in human fat in this country (Abbott et al, 1968).…”
Section: -2mentioning
confidence: 57%
See 2 more Smart Citations
“…The study reported here was undertaken jointly by the Laboratory of the Government Chemist (Department of Trade and Industry) and the Department of Health and Social Security on behalf of the Panel for the Collection of Residues Data of the Scientific Sub-Committee of the Advisory Committee on Pesticides and Other Toxic Chemicals. In its mode of operation it was very similar to the studies carried out in 1963-4 (Egan et al, 1965) andin 1965-7 (Abbott et al, 1968), but on this occasion the field was further extended to include Northem Ireland and also parts of south-west England; samples were also received from an additional centre in Scotland.…”
Section: Introductionmentioning
confidence: 88%